ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK AIR TANAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN MANGGARAI BARAT TAHUN 2019-2023 - Mayliana Yuandri Risna; Ni Made Dwita Ratnaningsih (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to analyze the effectiveness and contribution of groundwater tax revenue to the original revenue of West Manggarai Regency in 2019-2023. The data collection techniques used are documentation, literature studies, and interviews. The data sources used are secondary data, namely target data and realization of Groundwater Tax and target data and realization of West Manggarai Regency PAD for 2019-2023. The type of research used with quantitative descriptive analysis methods. The results showed that the effectiveness rate of the Groundwater Tax in West Manggarai Regency during the 2019-2023 period was very effective, reaching 113.63%. This shows that the Regional Government of West Manggarai Regency has been effective or good in managing the Groundwater Tax. Meanwhile, the level of contribution of Groundwater Tax to the increase in Regional Original Revenue (PAD) of West Manggarai Regency during the 2019-2023 period is still very less, only 2.29%. This shows that groundwater tax revenue has not been optimal